DARI SATIR DIGITAL KE CITRA POLITIK: ANALISIS FRAMING ROBERT ENTMAN TERHADAP PEMBERITAAN LAGU ‘MBG MAS BAHLIL GANTENG’ PADA KOMPAS.COM DAN CNNINDONESIA.COM - Fitri Dwi lestari (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2026)
This study aims to analyze the news framing of the "MBG Mas Bahlil Ganteng" song in Kompas.com and CNNIndonesia.com using Robert N. Entman's framing analysis model. The analysis was conducted on ten news articles, consisting of five articles from Kompas.com and five from CNNIndonesia.com, covering the viral phenomenon of the song on social media. The findings reveal that Kompas.com frames the "MBG Mas Bahlil Ganteng" song primarily as a digital cultural phenomenon by emphasizing netizens' creativity, entertainment, and participatory engagement in social media. In contrast, CNNIndonesia.com places greater emphasis on the political communication dimension, framing the song's virality as a phenomenon closely related to political image-building, public opinion management, and the communication strategies of political actors. Despite these different emphases, both media outlets reconstruct the song's original meaning, shifting it from a form of digital satire into narratives centered on entertainment and political image. These findings demonstrate that the media do not merely report reality but actively construct meaning through framing processes, thereby shaping public understanding of the relationship between digital culture, political satire, and political image-building in the digital media era.